2022
DOI: 10.1097/jnr.0000000000000501
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Professional Burnout in Nurses, Nursing Technicians, and Nursing Assistants During the COVID-19 Pandemic

Abstract: Background The COVID-19 pandemic may trigger sleep disorders and burnout in nursing professionals. Purpose This study was designed to describe the occurrence of sleep disorders and burnout in a nursing team during the COVID-19 pandemic and to identify the associated factors. Methods A cross-sectional approach was used. The questionnaire was administered via the Internet. All of the participants were nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…29 Nursing assistants and other frontline workers were disproportionately impacted compared to physicians and nurses. 3032 Contributing factors included lack of personal protective equipment (PPE), increased patient volume due to COVID-19, disruptions to workflow, social isolation, and perception of insufficient organizational and governmental support. 22,3337 A Colombian study reported that workers with an increased workload due to COVID-19 had ∼2 times higher odds of anxiety and depression compared to those without workload changes.…”
Section: Resultsmentioning
confidence: 99%
“…29 Nursing assistants and other frontline workers were disproportionately impacted compared to physicians and nurses. 3032 Contributing factors included lack of personal protective equipment (PPE), increased patient volume due to COVID-19, disruptions to workflow, social isolation, and perception of insufficient organizational and governmental support. 22,3337 A Colombian study reported that workers with an increased workload due to COVID-19 had ∼2 times higher odds of anxiety and depression compared to those without workload changes.…”
Section: Resultsmentioning
confidence: 99%
“… Problem/emotion-focused coping, sleep duration Burnout Blanco-Donoso et al (2021) Spain Cross sectional survey 56 physicians, nurses and nursing aids Hospitals To analyze if daily work-family conflict and burnout could explain the leaving intentions and vitality of healthcare workers Work-family conflict, job depersonalization, job emotional exhaustion Daily leaving intention, daily vitality Conyard et al (2020) Ireland Cross sectional survey 147 medical assistants Hospitals To investigate the frequency of burnout syndrome in medical assistants working in hospitals. Demographics: sex, assistant type, marital status Burnout Dos Santos et al (2022) Brazil Cross sectional survey 572 nurses and medical students Hospitals To describe the occurrence of sleep disorders and burnout in a nursing team during the COVID-19 pandemic and to identify the associated factors Working hours, sleep medications, sleep disorders Burnout Dreher et al (2021) Germany Cross sectional survey 2150 medical assistants Medical care centers, hospitals, and clinics To investigate pandemic-related stressors, attitudes, and work outcomes among medical assistants and to identify possible determinants Demographics, stressors, attitudes Depression, anxiety, work outcomes Ferriera and de Lucca, 2015 Brazil Cross sectional survey 538 nursing technicians Hospital To measure burnout among nurse technicians of working in a public hospital in the city of Campinas, São Paulo, and examine associations with sociodemographic and professional variables Gender, age, marital status, number of children, leisure activities, level of education, profession, and satisfaction at work Burnout Geiger-Brown et al (2004) United States Cross sectional survey 473 female nursing assistants Unionized nursing homes To explore the relationship between demanding work schedules and mental health indicators of depressive symptoms, depressive disorder, anxiety, and somatization among nursing assistants Work schedule Depression, anxiety, somatization Hochwälder (2008) Sweden Longitudinal surveys 838 nurses and 518 nurse assistants Hospitals To describe the relationship between empowerment and burnout Profession, gender, age, numbe...…”
Section: Resultsmentioning
confidence: 99%
“…One study found no correlation between gender and burnout ( Ferriera and de Lucca, 2015 ). Dos Santos et al reported that male participants experienced a higher prevalence of high and moderate levels of emotional exhaustion and depersonalization ( Dos Santos et al, 2022 ). In comparison, Navarro-Abal et al, found that women had significantly higher personal distress and empathetic concern compared to men ( Navarro-Abal et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…65 The importance of sleep quality and its disorders lies in the fact that it is a health indicator that influences quality of life and allows for better care, avoids the risk of procedural errors, better teamwork, and a lower risk of occupational accidents. 66 Sleep quality is also associated with eating imbalance patterns, since sleep quality facilitates the control of excessive intake and facilitates weight loss. 28 Additionally, poor sleep quality is associated with mood disorders, 67 which would intensify a poor perception of satisfaction.…”
Section: Discussionmentioning
confidence: 99%